The Prognostic Role of Glycemia in Patients With Pancreatic Carcinoma: A Systematic Review and Meta-Analysis - Wang, Xiaofang; Xu, Wanfeng; Hu, Xiaoru; Yang, Xianghong; Zhang, Mingming (Frontiers in Oncology, 2022)
Background: Fasting blood glucose and glycated hemoglobin (HbA1c) levels are associated with the risk of pancreatic cancer. Aim: To examine the relationship between perioperative glucose and HbA1c levels and prognosis in patients with pancreatic cancer. Methods: PubMed, Embase, and the Cochrane Library were queried for potentially eligible studies published up to May 2021. The exposures were perioperative fasting glucose and HbA1c levels. The primary outcome was survival. The secondary outcome was complications. All analyses were performed using the random-effects model. Results: Ten studies (48,424 patients) were included. The pre-operative (HR=1.10, 95%CI: 0.89-1.35; I2=45.1%, Pheterogeneity=0.078) and postoperative (HR=1.19, 95%CI: 0.92-1.54; I2=67.9%, Pheterogeneity=0.001) blood glucose levels were not associated with the survival to pancreatic cancer. Similar results were observed for HbA1c (HR=1.09, 95%CI: 0.75-1.58; I2=64.2%, Pheterogeneity=0.039), fasting blood glucose (FBG)/HbA1c (HR=1.16, 95%CI: 0.67-1.68; I2=0.0%, Pheterogeneity=0.928), and FBG (HR=1.75, 95%CI: 0.81-3.75; I2=79.4%, Pheterogeneity=0.008). Pre-operative blood glucose levels were not associated with postoperative complications (OR=0.90, 95%CI: 0.52-1.56), but postoperative glucose levels were associated with postoperative complications (OR=3.06, 95%CI: 1.88-4.97; I2=0.0%, Pheterogeneity=0.619). Conclusion: Blood glucose, FBG, and HbA1c levels are not associated with the survival of patients with pancreatic cancer. Postoperative blood glucose levels could predict postoperative complications.